2020
DOI: 10.3390/cells9071609
|View full text |Cite
|
Sign up to set email alerts
|

Show Me Your Friends and I Tell You Who You Are: The Many Facets of Prion Protein in Stroke

Abstract: Ischemic stroke belongs to the leading causes of mortality and disability worldwide. Although treatments for the acute phase of stroke are available, not all patients are eligible. There is a need to search for therapeutic options to promote neurological recovery after stroke. The cellular prion protein (PrPC) has been consistently linked to a neuroprotective role after ischemic damage: it is upregulated in the penumbra area following stroke in humans, and animal models of stroke have shown that lack o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 253 publications
(285 reference statements)
0
8
0
Order By: Relevance
“…PrP-knockout animal models subject to ischemia showed intensive ischemic damage and a reduced chance of regeneration whereas the possibility of PrP C synthesis resulted in PrP C overexpression and decreased ischemic damage [127]. Studies on ischemic strokes have indicated that PrP C overexpression can reduce the lesion size compared with wild-type mice, ascribing PrP C a protective role in ischemia damage [129][130][131][132][133][134][135]. After an ischemic insult, PrP C is associated with neuroprotective and regenerative processes by interacting with various cytosolic and transmembrane signal proteins.…”
Section: Prion Protein and Ischemic Strokesmentioning
confidence: 99%
“…PrP-knockout animal models subject to ischemia showed intensive ischemic damage and a reduced chance of regeneration whereas the possibility of PrP C synthesis resulted in PrP C overexpression and decreased ischemic damage [127]. Studies on ischemic strokes have indicated that PrP C overexpression can reduce the lesion size compared with wild-type mice, ascribing PrP C a protective role in ischemia damage [129][130][131][132][133][134][135]. After an ischemic insult, PrP C is associated with neuroprotective and regenerative processes by interacting with various cytosolic and transmembrane signal proteins.…”
Section: Prion Protein and Ischemic Strokesmentioning
confidence: 99%
“…AβPs reportedly inhibit the binding of Cu 2+ to PrP C [ 82 ]. PrP C contributes to AD pathogenesis as a toxic receptor of AβP oligomers [ 83 ]. Moreover, recent studies have suggested the involvement of PrP C in ischemia-induced neurotoxicity [ 84 , 85 ].…”
Section: Hypothetical Scheme Regarding Cu/zn Neurotoxicitymentioning
confidence: 99%
“…PRPC is expressed in neurons and glia, mainly on the cell surface as a glycosylphosphatidylinositol-anchored protein localized to lipid rafts. Though PRPC was, and understandably so, initially viewed as a bête noire, it is becoming clear that it serves many important physiological functions by interacting with extracellular and intracellular partners (Table 3) (Aguzzi et al, 2008;Castle and Gill, 2017;Didonna, 2013;Gavin et al, 2020;Linden, 2017;Miranzadeh Mahabadi and Taghibiglou, 2020;Peggion et al, 2017;Puig et al, 2020;Schneider et al, 2011;Sorgato et al, 2009;Watts et al, 2018;Wulf et al, 2017). Importantly, unlike APP, PRPC does not possess an intracytoplasmic tail and appears to act as a co-receptor serving as a conduit for various extracellular and membrane molecules.…”
Section: Prpc As a Receptor Mediating Aβ Effects On Memory Persistencementioning
confidence: 99%
“…See table of abbreviations for explanation of abbreviations. (See Aguzzi et al, 2008;Castle and Gill, 2017;Didonna, 2013;Liebert et al, 2014;Linden, 2017;Miranzadeh Mahabadi and Taghibiglou, 2020;Puig et al, 2020;Sorgato et al, 2009;Steinert, 2015;Watts et al, 2018;Wulf et al, 2017). Modulates NF-κB (NF-κB implicated in adult neurogenesis and structural plasticity).…”
Section: Trem2mentioning
confidence: 99%